MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2004)
MALAYSIA AMONG WORLD'S TOP THREE CONTENDERS FOR OFFSHORING BUSINESS Malaysia is among the top three contenders for offshoring business in the world according to the 2004 Offshore Location Attractiveness Index compiled by the global management consulting firm A.T. Kearney, sources were quoted. Malaysia is ranked 3rd behind India (1st) and China (2nd) but ahead of Singapore (5th), Philippines (6th) and Thailand (13th). In its report, A.T. Kearney considers Malaysia a “natural choice” for offshore services in view of its low costs, particularly for infrastructure, the most attractive business environment among emerging markets, strong global exposure of the workforce, and government support for the information and communications technology (ICT) sector. Other significant initiatives cited by A.T. Kearney include the government’s investments in infrastructure and developing the intelligent cities of Cyberjaya and Putrajaya as part of the Multimedia Super Corridor project. Thus, numerous companies – Motorola, Ericsson, IBM, Shell, DHL, HSBC and BMW- have located their regional offshore service centers in Cyberjaya.